Analysis of the Influence of Technology in Creating a Smart City: Systematic Literature Review - Widian Nigrum; Elfitri Oktavia; Nurhasan Syah; Heldi Heldi; Indra Catri (Science and Environmental Journal for Postgraduate, 2024)
The concept of Smart City is a concept that has gone through the refinements of the ideas that have previously developed by patching existing shortcomings and considering aspects that may not yet exist in the concepts based on Information and Communication Technology (ICT) that have appeared before. The role of technology in the Smart City has two sides that must be noted, in addition to providing many great opportunities, it can also cause vulnerability if the technology is misused or applied in a dangerous or deviant manner and without adequate provisions. This type of research is research that uses the systematic review method (Systematic Review). The stages of literature collection refer to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. The results of this research show that digital technology can be applied to build a smarter city that responds to the needs of the community. Innovation and digital technology can change, replace, or complement existing standards in certain companies, ecosystems, and sectors. Digital transformation is the most important part of the Smart City concept because it can improve efficiency, quality of life, and various aspects of urban life. In addition, technology and digital play an important role in changing the urban landscape in digital transformation.